Certificación del cableado estructurado de categoría cat 6, en el laboratorio de redes de la Universidad Técnica de Cotopaxi extensión La Maná - Cunuhay Cuchipe, Hernán Darío (2016)
Certification is a process in which was compared the performance, connectivity and operation of structured cabling CAT 6, was applied tests in CAT 6 U/UTP channel (Patch Cord included) an operating frequency of 250 MHz respectively, as described by the standard T568C.2 into 32 data points installed in the network Laboratories at Cotopaxi Technical University La Mana....